The Effect of Moringa Leaf Powder (Moringa oleifera L) in the Diet on the Production Performance of Quail Eggs (Coturnix coturnix japonica) - Urip Santoso (Universitas Tidar, 2021)
This study aims to evaluate the effect of Moringa leaf powder (Moringa oleifera L) in the diet on the performance of quail egg production. This research was conducted for 8 weeks at the Commercial Zone Animal Laboratory, Department of Animal Science, Faculty of Agriculture, Bengkulu University. The experimental design used in this study was a completely randomized design with 5 treatments with 5 replications and each replication consisted of 5 quails. The treatment given was P0 as a control; P1 ration contained 0.5% commercial feed supplement; P2 ration contained 0.5% Moringa leaf powder; P3 ration contained 1.5% Moringa leaf powder; P4 ration contained 2.5% Moringa leaf powder. The results showed that the Moringa leaf powder in rations up to a level of 2.5% had no significant effect (P>0.05) on feed intake, egg weight, egg production, egg mass production, and feed conversion ratio. Based on the results of the study, it was concluded that the administration of 0.5% Moringa leaf powder could replace commercial feed supplements. The higher levels of Moringa leaf powder administration did not improve egg production performance. The addition of commercial feed supplement in quail rations was not necessary.